(untitled) (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study aims to explore the forms and dynamics of learning democratization at Wahdah Islamiyah Integrated Islamic Junior High School in Makassar through the perspectives of ethics and law, and its influence on shaping Islamic cultural behavior. Using a phenomenological approach with observation, interviews, and documentation, the research reveals that democratized learning is characterized by active and participatory methods such as experiential learning, group work, discussions, presentations, feedback, and role-playing. These practices encourage stronger meaning-making, correction of misconceptions, and social interaction among students. From the perspective of ethics and law, democratization fosters a peaceful, stable, and harmonious school environment by regulating relationships between students and educators. Ethics guide behavior in accordance with social and moral norms, while law prevents harmful actions and provides accountability. Together, they form complementary foundations in nurturing sustainable Islamic cultural behavior, grounded in tawhid, akhlaq, and knowledge as integral elements of Islamic civilization encompassing aqidah, sharia, and muamalah.